2014
DOI: 10.1080/01916122.2013.846280
|View full text |Cite
|
Sign up to set email alerts
|

Plant sources for bee pollen load production in Sergipe, northeast Brazil

Abstract: In Brazil, the production of bee pollen loads began modestly in the late 1980s, stimulated by consumption of natural products. Demand and consumption have increased, and there has been no increase in scientific studies. This work aims to expand scientific knowledge by identifying the plants used by Apis mellifera L. as sources of pollen loads in the State of Sergipe, Brazil. Twelve samples were collected from January to December 2011, in the municipalities of Barra dos Coqueiros, Brejo Grande, Estância and Pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 18 publications
0
13
1
1
Order By: Relevance
“…Besides quantity [ 6 ], the diversity of collected pollen is important for honey bee health [ 7 , 8 ]. Honey bee colonies forage on an area of more than 10 km 2 and several studies have reported on the diversity of collected pollen [ 2 , 9 12 ]. But the ways in which land use change and agricultural intensification influence the amount and diversity of collected pollen remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Besides quantity [ 6 ], the diversity of collected pollen is important for honey bee health [ 7 , 8 ]. Honey bee colonies forage on an area of more than 10 km 2 and several studies have reported on the diversity of collected pollen [ 2 , 9 12 ]. But the ways in which land use change and agricultural intensification influence the amount and diversity of collected pollen remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…are an important plant for the generation of bee pollen in apiaries of the Brazilian Northeast (Alves;Santos, 2014). In the southern coast of the northeastern state of Bahia, Brazil (city of Canavieiras), Dórea, Novais and Santos (2010) collected bee-pollen with high relative frequencies of Elaeis, M. pudica and Cecropia pollen types.…”
Section: Bee Pollen Sourcementioning
confidence: 99%
“…Apiculture meets the requirements of sustainability in the agriculture sector and is one of the few activities in the northeast region of Brazil that represents a new dynamic for income management, since the biome and tropical climate in this area provides food and development conditions for bees throughout the year (Alves;Santos, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Attalea speciosa was present in the diet of bees throughout the year, becoming dominant in November, December and August. Studies on pollen production in other regions of the northeastern Brazil reported that species of Arecaceae (e.g., Cocos nucifera) are always frequent throughout the year in the diet of honeybees, emphasizing the importance of this family for A. mellifera (Almeida-Muradian et al, 2005;Arruda et al, 2013;Alves & Santos, 2014).…”
Section: Discussionmentioning
confidence: 99%